The Role of Firm Reputation and Management Experience for Firm Performance after Merger and Acquisition - Edi Edi; Erni Susanti (Jurnal Reviu Akuntansi dan Keuangan, 2021)
This study examines the impact of firm reputation and CEO experience to company performance after merger and acquisition. The sample of this research are companies listing on the Indonesia Stock Exchange and register their M&A action to the Indonesian Commission for the Supervision of Business Competition. The time frame for selecting data is from 2014 to 2019. The research data are tested and analyzed with multiple linear regression methods on SPSS Software by using 110 sample data. The results of the data test prove that the acquisition experience in the same industry and the measurement of the company's capitalization reputation have a significant positive impact on company performance. Following the concept of knowledge transfer theory and organizational theory, acquisition in same industry will increasing company value and performance in competing with other competitors with more focused and can create cost saving. These will have an effect on company performance by get a good response in public and achieve a competitive advantage. Novelty of this research provides a new insight for firm reputation measurement that are still relevant to be used for measure firm reputation.